Implementation of Work From Home (WFH) Policy During the Covid-19 Pandemic at SDN Kepanjen 01 Kepanjen Malang Regency - Dewik Wulan Prihatiningsih; Sri Untari; Syamsul Hadi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research is a quantitative descriptive study with an instrument in the form of a questionnaire. Data analysis was carried out in two ways, quantitative data was analyzed by non-parametric statistics and qualitative data was classified through coding. The population and sample of this study were all 12 teachers. The results showed that (1) all teachers at SDN Kepanjen 01 Kepanjen District, Malang Regency carried out WFH according to the Government Circular Letter, namely the learning planning stage: using it for making lesson plans and discussing with fellow teachers; stages of the learning process: using google forms and WA for student attendance, zoom for delivering material, WA for giving and collecting assignments, youtube and the web for learning media; and the learning evaluation stage: using google forms for PH or PTS and gadgets to correct student evaluation results. (2) The implementation of WFH at SDN Kepanjen 01 encountered various obstacles. (3) Obstacles during WFH are categorized into obstacles in gadgets, internet, material understanding, finance, communication, and level of focus. (4) The solution to the problems experienced is adjusted to the situation and condition of teachers and students' families at SDN Kepanjen 01 so that WFH and BDR can still run optimally. (5) WFH has a positive impact, namely creating a feeling of security because it avoids the spread of covid-19, has more free time, is free to determine work schedules, and automatically reduces transportation costs. While the negative impact is that teachers experience boredom, reduced interaction with colleagues, lowers the quality of performance results, and is addicted to social media. The researcher's suggestions for teachers are that teachers should (1) implement whatever policies have been set by the Principal with full responsibility and enthusiasm; (2) discuss all the obstacles that arise during WFH with the Principal and fellow teachers in order to obtain the most appropriate solution; (3) always teach students to apply health protocols at home; and (4) although WFH has a negative impact, teachers must be able to overcome it in various ways so as not to affect the quality of learning for students.